Effects of problem‐based learning on delivering medical and nursing education: A systematic review and meta‐analysis of randomized controlled trials. - Ren, Song; Li, Yi; Pu, Lei; Feng, Yunlin (Worldviews on Evidence-Based Nursing (John Wiley & Sons, Inc.), 2023)
Background: There is still a lack of high‐level evidence on the effects of problem‐based learning (PBL) in general medical and nursing education. Aims: We aimed to summarize current evidence on the effects of PBL in delivering medical and nursing education from randomized controlled trials (RCTs). Methods: A systematic search was performed in MEDLINE, EMBASE, Cochrane Central Library, and CINAHL Complete. RCTs that assessed the effects of a PBL module in delivering medical education were eligible. Outcomes included knowledge, performance, and satisfaction. The risk of bias was assessed according to Cochrane handbook guidelines. Standardized mean differences with 95% confidence intervals of each outcome between PBL and control groups were pooled using a random‐effects model. Results: In all, 22 RCTs with 1969 participants were included. Both pooled analyses of changes in scores compared with baseline and absolute post‐interventional scores favored PBL module in knowledge and performance. The satisfaction degree was also higher in participants receiving PBL methods. Publication bias might exist in satisfaction; however, not in knowledge and performance. Eleven of the 22 studies were assessed as having a high risk of bias. Linking Evidence to Action: Compared with traditional lecture‐based modules, PBL delivered medical education in different medical science specialities more efficiently from both theoretical knowledge and practice skill perspectives. The feedback from participants receiving PBL methods was more positive than that from those receiving traditional methods. However, the high heterogeneity and low quality of the included studies prevented drawing definite conclusions.